Improved Ultraviolet Radiation Film Dosimetry Using OrthoChromic OC‐1 Film†. (28th December 2020) - Welch, David; Brenner, David J.
Abstract: There is growing interest in far‐UVC lighting, defined as wavelengths from 200 to 230 nm, because research has demonstrated these wavelengths to be an effective antimicrobial technology while posing a minimal hazard to human health. Far‐UVC lighting is now being installed to directly irradiate spaces where humans are present, and it will be important to perform measurements to verify far‐UVC lighting installations are operating within widely accepted exposure guidelines. In this work, we explore the use of a commercially available film, known as OrthoChromic OC‐1, to measure ultraviolet radiation exposure. The film was tested with a variety of ultraviolet wavelengths and irradiance conditions, and the color change of the film was analyzed for increasing levels of radiant exposure. The film response extended over a dynamic range that was greater than the recommended exposure limits for far‐UVC radiation so it can potentially be useful for health hazard monitoring. The spectrum of the incident ultraviolet radiation strongly affected the response of the film; therefore, for accurate measurements we recommend the measured spectrum match the spectrum used for calibration. Overall, dosimetry with this film provides a simple, accurate, and inexpensive method of quantifying ultraviolet radiation exposure that is suitable for far‐UVC measurements. Abstract : In this work, we explore the use of a commercially available film, known as OrthoChromic OC‐1, to measure ultraviolet radiation exposure. The film was tested with a variety of ultraviolet wavelengths and irradiance conditions, and the color change of the film was analyzed for increasing levels of radiant exposure. Dosimetry with this film provides a simple, accurate, and inexpensive method of quantifying ultraviolet radiation exposure that is suitable for far‐UVC measurements.